2020
DOI: 10.32553/ijmbs.v4i6.1168
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal Outcome in Post Dated Pregnancy: A Retrospective Study

Abstract: Introduction: Postdated pregnancy is defined as pregnancy extended beyond 40 weeks of gestation or 280 days. FIGO and WHO defined post term pregnancy as a pregnancy which has gestational length of 294 days or more, Post term pregnancy is defined as pregnancy that has extended to or beyond 42 weeks of gestation, or estimated date of delivery (EDD)+14 days. Therefore we conducted this study to evaluate fetomaternal outcome in post dated pregnancies. Material & Methods: This was a retrospective hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In the study done by Kandalgaonkar et al and Agarwal et al similar results were found where majority had bishop's score <4. 16,17 In this study, 43% cases delivered with spontaneous onset of labour and 57% cases were induced. Induction of labour is more likely to succeed when the cervix is favourable.…”
Section: Discussionmentioning
confidence: 59%
“…In the study done by Kandalgaonkar et al and Agarwal et al similar results were found where majority had bishop's score <4. 16,17 In this study, 43% cases delivered with spontaneous onset of labour and 57% cases were induced. Induction of labour is more likely to succeed when the cervix is favourable.…”
Section: Discussionmentioning
confidence: 59%
“…The occurrence of jaundice in the neonatal stage was documented to be around 20%. The elevated percentage of jaundice may be a direct result of forceps delivery having a higher incidence [24]. Another study documented the percentage of neonatal jaundice to be as high as 40% while a meager 2% was accounted for hypoglycemia and an even less 1% accounting for birth asphyxia [25].…”
Section: Discussionmentioning
confidence: 99%
“…Another study documented the percentage of neonatal jaundice to be as high as 40% while a meager 2% was accounted for hypoglycemia and an even less 1% accounting for birth asphyxia [25]. A different study revealed increased changes of Apgar being less than seven, extremely less weight at birth, admission into the neonatal intensive care unit (NICU), and belated breastfeeding linked with labor induction [24].…”
Section: Discussionmentioning
confidence: 99%